The Effect of Foreign Interests and Multinationals on Tax Aggressiveness in Indonesia - Jimmy Evaldo Prakasa; Rachmawati Meita Oktaviani (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
Tax is one of the sources of state revenue and provides a significant contribution to the state treasury. In-Law Number 28 of 2007 Article 1 Paragraph 1 it is stated that tax is a mandatory contribution that is forced and levied from individuals or entities for the state. Taxes levied by the state are used to realize the general benefit for both the state and the people. The realization of the usefulness of paying taxes can be seen by the growing growth of facilities and infrastructure throughout Indonesia purpose of this study was to determine the effect of the characteristics of multinational companies on tax aggressiveness. the characteristics of multinational companies include foreign interests, as indicated by foreign ownership, and foreign ownership; and oversees company operations (multinationality) in companies listed on the Indonesia Stock Exchange for the 2016-2019 period. This study uses a quantitative method by applying statistical calculations. The number of data samples in this study was 280 data from all companies listed on the IDX and used the purposive sampling technique for sample selection. The tests used to analyze this consist of model testing, classical assumption test, panel data regression test, coefficient of determination test, simultaneous test (f test), and partial test (t-test). The test results show that multinationality has an effect on tax aggressiveness, foreign and foreign ownership has no effect on tax aggressiveness